A Research on Functional Status, Environmental Conditions, and Risk of Falls in Dementia. (19th May 2014) - Eshkoor, Sima Ataollahi; Hamid, Tengku Aizan; Nudin, Siti Sa'adiah Hassan; Mun, Chan Yoke
Abstract : This study aimed to determine the effects of disability, physical activity, and functional status as well as environmental conditions on the risk of falls among the elderly with dementia after adjusting for sociodemographic factors. Data were derived from a group including 1210 Malaysian elderly who were demented and noninstitutionalized. The study was a national cross-sectional survey that was entitled "Determinants of Health Status among Older Malaysians." Approximately 17% of subjects experienced falls. The results showed that ethnic non-Malay( OR = 1.73 ) and functional decline( OR = 1.67 ) significantly increased the risk of falls in samples (P < 0.05 ). The findings indicated that increased environmental quality( OR = 0.64 ) significantly decreased the risk of falls (P < 0.05 ). Disability, age, marital status, educational level, sex differences, and physical activity were found irrelevant to the likelihood of falls in subjects (P > 0.05 ). It was concluded that functional decline and ethnic non-Malay increased the risk of falls but the increased environmental quality reduced falls.